Parents’ perceptions and experiences of physical activity in childhood cancer survivors in Singapore: a qualitative study - Lindsey Jean Ross Weller; Debbie Grant Cavers; Neneh Rowa-Dewar (Singapore Medical Journal)
Introduction: The survival rate for childhood cancer has increased with advances in medical care. Along with this comes the growing burden of long-term side effects of cancer treatment and cancer survivorship. Childhood cancer survivors are more likely to be sedentary and have a lower quality of life. Physical activity (PA) can promote health and well-being in childhood cancer survivors, but few studies have explored the role of parents of childhood cancer survivors (PCCS) in promoting PA. This qualitative study aims to explore the perceptions of PCCS in Singapore and the role they may have with regard to PA. Methods: Participants were recruited through a local charity via email, social media and posters. One-hour semi-structured interviews were conducted online with seven parents. With consent, the interviews were recorded, transcribed verbatim and analysed using thematic analysis. Results: Our study discussed thematically parents’ accounts on (1) the barriers and enablers of PA and (2) the complications of cancer that potentially affect the levels of PA in childhood cancer survivors. Parents reported that childhood cancer negatively affects the quality of life and participation in PA. The determinants of participation in PA were multifaceted, and socioecological and health belief models were used to demonstrate how these factors were interlinked. Conclusion: Participation in PA is influenced at an individual, family, community and societal level. The improved understanding facilitated by this research can be used to shape paediatric cancer care practices in Singapore and guide institutional or national policy interventions.